Relationship between exposure to message framing of federalism and college students' intention to support the federal government campaign - Olar, Allan Jeo I. (2019)
This study examined the relationship of exposure to message framing on federalism and the intention of the college students to support the federal government campaign. The change of government structure has constituted major implications on the current legislative, judiciary, and executive branches of the state. The amplification/attenuation of information on federalism affected the individuals? knowledge, attitude, and intention to support the federal government campaign of the Duterte Administration. Using the Pretest-Posttest design, this study was conducted among 80 student participants of the lecture on Federalism. Mann-Whitney U and Wilcoxon Signed Rank Test revealed that there was no significant difference among the variables tested. The participants of both lectures increased their knowledge on federalism; however, the beliefs and intention of the participants on federalism reflected no changes at all. Single exposure to lectures on federalism did not justify the change of students? attitude on federalism; hence, there were no changes on their existing intention on the matter. The results showed that students had a low intention and quite-negative attitude on the proposed charter change and federalism.